2016
DOI: 10.1161/circheartfailure.115.003116
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Heart Failure With Preserved and Reduced Ejection Fraction

Abstract: Background Heart failure (HF) is a prevalent and deadly disease, and preventive strategies focused on at-risk individuals are needed. Current HF prediction models have not examined HF subtypes. We sought to develop and validate risk prediction models for HF with preserved and reduced ejection fraction (HFpEF, HFrEF). Methods and Results Of 28,820 participants from four community-based cohorts, 982 developed incident HFpEF and 909 HFrEF during a median follow-up of 12 years. Three cohorts were combined and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
200
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 272 publications
(215 citation statements)
references
References 52 publications
9
200
1
5
Order By: Relevance
“…The differences in baseline characteristics between the male and female patients of this study are also similar to what has been previously reported in the literature for higher diastolic blood pressure (dBP), hematocrit levels, ejection fraction, and diabetes [10,[19][20][21]. There have also been reports that biomarkers, such as BNP, have a sexual bias in predicting cardiac outcome.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The differences in baseline characteristics between the male and female patients of this study are also similar to what has been previously reported in the literature for higher diastolic blood pressure (dBP), hematocrit levels, ejection fraction, and diabetes [10,[19][20][21]. There have also been reports that biomarkers, such as BNP, have a sexual bias in predicting cardiac outcome.…”
Section: Discussionsupporting
confidence: 87%
“…Compared to females, heart failure in males has been associated with lower ejection fraction and slower heart rate; males may also have elevated levels of brain natriuretic peptide (BNP), higher creatinine and galectin-3 levels, higher diastolic blood pressure (dBP), and are more likely to be diabetic [11,[20][21][22]. Thus, in light of the paucity of information regarding sex differences, oxidative stress, and CHF, we conducted a study with the purpose of measuring a global biomarker of oxidative stress in both sexes hospitalized for CHF to determine if oxidative stress is differentially expressed in males and females under these conditions and if there is a difference based on acute outcome.…”
Section: Introductionmentioning
confidence: 99%
“…HFpEF represents a complex clinical syndrome with multiple comorbidities, such as hypertension, diabetes mellitus, renal disease, metabolic syndrome, and atrial fibrillation . Systemic hypertension is the most prevalent modifiable risk factor, and its presence confers an increased risk of developing clinically apparent heart failure …”
mentioning
confidence: 99%
“…With respect to comorbidities, black and Hispanic patients had higher rates of diabetes, hypertension, and renal insufficiency. These findings suggest that the known risk factors for HFpEF are more prevalent among minority patients (5,6). These differences in comorbidities according to race/ethnicity among patients with HFpEF is consistent with the observed trends in cardiovascular risk factors among minorities nationally, in which the prevalence of obesity, poorly controlled hypertension, and diabetes has increased (10).…”
Section: Discussionmentioning
confidence: 80%
“…Hypertension is the strongest known risk factor for HFpEF, along with age, obesity, and diabetes mellitus (5,6). Among hospitalized Medicare patients with HF, those with HFpEF have an observed lower mortality but higher readmission rate compared with those with HFrEF (7).…”
mentioning
confidence: 99%